Enhancement of phenolic acid content and antioxidant activity of rice bran fermented with Rhizopus oligosporus and Monascus purpureus. Issue 1 (January 2015) - Abd Razak, Dang Lelamurni; Abd Rashid, Nur Yuhasliza; Jamaluddin, Anisah; Sharifudin, Shaiful Adzni; Long, Kamariah
Abstract The effect of solid-state fermentation using several types of fungi on the phenolic acid content and antioxidant activity of rice bran (RB) was determined and compared to the non-fermented counterpart. The substrate was fermented with single and mixed cultures of two types of fungi: Rhizopus oligosporus and Monascus purpureus. The total phenolic content (TPC), determined using the Folin–Ciocalteu method, increased upon fermentation. The antioxidant activity was analyzed using the ferric reducing ability of plasma (FRAP) method, which showed the same trend as TPC; that is, the antioxidant activity improved in all fermented samples. In contrast to the TPC and FRAP assays, the DPPH (2, 2-diphenyl-1-picrylhydrazyl) radical-scavenging activity of the fermented samples exhibited either an insignificant improvement or reduced activity. The phenolic acid content in methanol extracts of fermented RB, determined using high performance liquid chromatography (HPLC), generally showed a significant increase in ferulic, sinapic, vanillic, caffeic, syringic, and 4-hydroxybenzoic acids. The results of this study prove that the overall antioxidant activity and phenolic acid content of RB can be enhanced by solid-state fermentation using fungi.